Thiết kế các ngôn ngữ mô tả và xây dựng cơ sở tri thức cho các phần mềm trợ giúp giải bài toán hình học - Thủy, Nguyễn Thanh (Journal of Computer Science and Cybernetics, 2016)
Our purpose is to present some fundamental principles for designing an interface language FCL and three languages SCL, CDL and LDL and their impact on the development of an ITS for figure correctness verification and geometry problem proof. Besides, LDL predicates are used for expressing almost geometry theorems and properties in a knowledge base over which an ITS makes inference. Some experimental of ITS are implemented in the Borland C++, version 3.1.